Indigenous multiresistant bacteria of Cupriavidus pauculus IrC4 isolated from Indonesia as a heavy metal bioremediation agent - Irawati Wahyu; STEVANUS ERICK WINOTO; LUCIA KUSUMAWATI; REINHARD PINONTOAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Irawati W, Winoto SE, Kusumawati L, Pinontoan R. 2021. Indigenous multiresistant bacteria of Cupriavidus pauculus IrC4 isolated from Indonesia as a heavy metal bioremediation agent. Biodiversitas 22: 3349-3355. Heavy metal pollution is a serious environmental problem because it endangers humans, animals, and plants. Bioremediation of heavy metals using bacteria is an effective method to remove heavy metals. Cupriavidus pauculus IrC4 is an indigenous multi-resistant bacteria isolated from Indonesia. This study aims to determine the growth of this strain in a medium containing cadmium, mercury, lead, copper, and its ability to accumulate heavy metal. Bacterial resistance was observed by cultivating bacteria on a Luria Bertani medium containing various concentrations of heavy metals. Heavy metal accumulation was measured using atomic absorption spectrophotometer. The study showed that this strain could grow in a solid medium containing 5 mM cadmium, 13 mM lead, and 4 mM mercury, also in 0.5 mM of the heavy metal mixture. A high concentration of heavy metals resulted in lag phase elongation and logarithmic growth phase inhibition. C. pauculus IrC4 could accumulate copper, lead, and cadmium and lead up to 371.42 mg, 254.4 mg, 5.8 mg heavy metals per gram of dry weight of cells, respectively. In conclusion, this strain is a promising bacterium for use as a heavy metal bioremediation agent.